Extended resections and other special cases in lung cancer surgery: Real‐world population‐based outcomes. Issue 10 (1st September 2020) - Helminen, Olli; Valo, Johanna; Andersen, Heidi; Söderström, Johan; Sihvo, Eero
Abstract : Background: Lung cancer invading outside a lobe centrally or peripherally, or presenting with synchronous or metachronous tumors, requires a special approach. Here, we aimed to evaluate the rate and outcomes of surgery of these patients in a medium‐volume practice using real‐world, population‐based data. Methods: All patients ( n = 269) on whom lung cancer surgery was performed in Central Finland and Ostrobothnia between January 2013 and December 2019 were included. A total of 40 patients with sleeve ( n = 18) or other extended resections ( n = 9), multifocal diseases ( n = 14), and other operated synchronous cancers ( n = 3) required an extended or otherwise special surgical approach (extended group). Short‐ and long‐term outcomes were compared to high‐risk ( n = 72) and normal patient groups ( n = 157). Results: The rate of extended resection was 14.9%. The rates of PET‐CT (95%), invasive staging (35%), and brain imaging (42.5%) were highest in extended group compared to other groups. Extended group had larger and higher rate of stage III tumors than high‐risk and normal groups. All extended group patients underwent anatomic lung resection with better lymph node yield than the other two groups, with a neoadjuvant and/or adjuvant treatment rate of 70.0%. Major complications occurred in 7.5% in the extended group, 19.4% in the high‐risk group, and 6.4% in the normal group; at one year, alive and living at home rates were 88.2%, 83.3%, and 97.8%, and overall five‐year survival rates 75.6%, 62.4%, and 63.9% ( P = 0.287), respectively. Conclusions: After guideline‐based evaluation, a significant rate of these special cases can be resected with a low complication rate and good long‐term survival in real‐world practice. Key points: Significant findings of the study: Extended resections for lung cancer include tumors spreading outside the lung The rate of extended resection was 14.9% in a population‐based setting Major complications occurred in 7.5% and five‐year survival was 75.6% What this study adds Complication rate and long‐term outcome were similar compared to normal patients Guideline‐based evaluation results with excellent outcome in real‐world practice Abstract : Extended resections for lung cancer include tumors spreading outside the lung. In this population‐based study, the rate of extended resection was 14.9% with major complications occurring in 7.5% and five‐year survival was 75.6%. Guideline‐based evaluation results with excellent outcome in real‐world practice.